Effectiveness of learning mathematics derivative materials using modules equipped with cooperative models in high schools - Jitu Halomoan Lumbantoruan; Risma Uly Manalu (Institute of Advanced Engineering and Science, 2024)
The aim of the research is to improve the learning outcomes of mathematics material in high schools. At the high school level, there are three materials that are difficult for students to understand, one of which is derivative material. In fact, student learning outcomes in low-derived material. Difficulties arise because teachers rarely write teaching modules. There is difficulty understanding the definition (71.42%), concepts (71.42%), principles (57.14%), and skills (42.85%). In the needs analysis, 90% of students had difficulty with derivative material and the teacher was of the opinion that 85% of students had low scores on derived material. The research used research and development (R&D) method. The stages of research are needs analysis, design, development, implementation, and evaluation. As a result, the validation of material experts is 91.72%, math teachers are 92.42%, and students are 95.90%, all three are categorized as very good. Students who do not use the module get an average score of 65.51, and students who are assisted by the module get an average score of 87.20. In conclusion, there is a significant difference between using a module and not using a module of 21.69. The research interprets the developed modules to significantly improve student learning outcomes.